The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/acp.3521
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of child investigative interviewing in the Netherlands

Abstract: Using evidence-based guidelines to interview children is an important means to obtain complete and accurate accounts. In the current study, we examined the quality of child investigative interviewing in the Netherlands. To examine this, we compared the Dutch Scenario Model with the National Institute of Child Health and Human Development Protocol and interviews from countries that did not follow a specific protocol. Our principal result was that Dutch child interviewers rarely asked recommended open prompts th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…We fully agree that the first empirical paper on the quality of the Scenario Model has limitations (Otgaar et al, ). Like Rispens et al (in press) correctly stated, we only concentrated on the type of questions used in the Scenario Model interviews, to estimate interview quality, a strategy that has been used in previous studies (e.g., Cyr & Lamb, ; Orbach et al, ).…”
Section: Points Of Agreementsupporting
confidence: 85%
See 1 more Smart Citation
“…We fully agree that the first empirical paper on the quality of the Scenario Model has limitations (Otgaar et al, ). Like Rispens et al (in press) correctly stated, we only concentrated on the type of questions used in the Scenario Model interviews, to estimate interview quality, a strategy that has been used in previous studies (e.g., Cyr & Lamb, ; Orbach et al, ).…”
Section: Points Of Agreementsupporting
confidence: 85%
“…In a recent paper (Otgaar et al, ), we reported on the first empirical investigation into the Scenario Model, an interview method used by the Dutch police to interview alleged child victims of abuse. We found that open prompts, known to elicit detailed and accurate statements in children, were rarely used.…”
mentioning
confidence: 99%
“…In our opinion, Otgaar and colleagues () state wrongly that the Scenario Model does not focus on the continuous use of open‐ended prompts. In handouts, guidance books, e‐learning modules, and training of the Scenario Model, there is much emphasis on different types of questions and their effect on the retrieval of children's memory (Dekens & Van der Sleen, ).…”
Section: Misunderstandings About Scenario Modelmentioning
confidence: 92%
“…Otgaar and colleagues () judged interviews as “high quality” if open prompts (cued invitations) predominated and as “low quality” if directives and option‐posing questions predominated. In our opinion, their definition of a good interview might be too narrow, since other indicators of a good interview, like the absence of suggestive questions, can be specified.…”
Section: Definition Of Qualitymentioning
confidence: 99%
See 1 more Smart Citation